2005
DOI: 10.1182/blood-2004-12-4630
|View full text |Cite
|
Sign up to set email alerts
|

Regional induction of adhesion molecules and chemokine receptors explains disparate homing of human B cells to systemic and mucosal effector sites: dispersion from tonsils

Abstract: Ethical constraints restrict direct tracking of immune-cell migration throughout the human body in vivo. We, therefore, used deletion of the immunoglobulin M (IgM) heavy-chain constant-gene (C) segment as a marker to provide a dispersal signature of an effector B-cell subset (IgD ؉ IgM ؊ CD38 ؉ ) induced selectively in human tonsils. By DNA analysis, the C deletion identified dissemination of such blasts and their plasma-cell progeny to peripheral blood, lymph nodes, and bone marrow, as well as to mucosae and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 57 publications
7
113
0
Order By: Relevance
“…Mucosal B cells from adenoids home preferentially to mucosae and glands of the upper airways [41]. Although the phenotype of the antibody-secreting cells that generated the IgG detected in our cultures was not determined, dual staining of immunocytes for IgG and immunoglobulin J chain showed that some IgG + immunocytes, from adenoids but not from PBMC, co-express J chain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal B cells from adenoids home preferentially to mucosae and glands of the upper airways [41]. Although the phenotype of the antibody-secreting cells that generated the IgG detected in our cultures was not determined, dual staining of immunocytes for IgG and immunoglobulin J chain showed that some IgG + immunocytes, from adenoids but not from PBMC, co-express J chain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are required to demonstrate which soluble factors are responsible for the proliferation of B cells by supernatants from C. jejuni-activated DCs and whether B cells show gene rearrangements and maturate into Ab-producing plasma cells in this particular context. In addition, future studies should account for the various enteric and tonsillar B cell subsets, which may differ in the expression of homing receptors (39).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated SI LP, MLN, and SP lymphocytes were stained with different combinations of GFP-VLP and the following anti-mouse Abs (all obtained from BD Pharmingen unless specified): IgA FITC (Southern Biotechnology Associates); B220 PerCP (RA3-6B2); ␣ 4 ␤ 7 PE or allophycocyanin (DATK32.2, allophycocyanin-labeled by Chromoprobe); CCR9 allophycocyanin (242503; R&D Systems); CD138 PE (281-2); and a dump PE or biotin, which included Thy 1.2 (53-2.1), CD-11c (HL3), CD-11b (M1/7), and IgD (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). After staining, cells were washed once and fixed with 1% paraformaldehyde (Electron Microscopy Sciences).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Because of the variety of tissues in which CCL28 is expressed, it was suggested that the CCL28/CCR10 interaction may function as a unifying mucosal homing mechanism for IgA ϩ plasmablasts/PC (17). However, it has recently been shown that nasal-associated lymphoid tissuederived human B cells, which also express CCR10, have limited access to the SI because they express low levels of CCR9 and ␣ 4 ␤ 7 (18). Hence, the coexpression of homing and chemokine receptors contributes greatly to the compartmentalization of the mucosal immune system, with important implications for the development of effective vaccines (19).…”
mentioning
confidence: 99%